Eksistensi Mahasiswa dalam Peningkatan Akademik Melalui Program Kampus Mengajar di SDN 04 Purwosari Kecamatan Comal Kabupaten Pemalang - Nova Indriyani Cahyaning Tias; Septi Indriyani; Diana Rahmawati; Bahtiar Yasin; Fahrur Rizal; Anita Damayanti; Suranto Suranto (Jurnal Surya Masyarakat, 2022)
The COVID-19 pandemic that is currently happening in Indonesia has had a major impact in all fields, one of which is education. In this pandemic period, education in Indonesia must be carried out online, which results in the inhibition of direct interaction between teachers and students. Therefore, the Ministry of Education and Culture organizes a Teaching Campus program, which is part of the Independent Learning Campus (MBKM) policy. This Teaching Campus Program aims to provide solutions for elementary schools affected by the pandemic by empowering students who live around the school area to assist teachers in carrying out learning activities in the midst of the COVID-19 pandemic. The results of the study show that the implementation of the Class 2 Teaching Campus at Public Elementatry School 04 of Purwosari includes the following: First, teaching is carried out by home visits, through online media, and face-to-face (after limited PTM verification). Second, technology adaptation by helping teachers prepare materials sent via WhatsApp media, and third, assisting administration in the form of allocating textbooks in libraries and collecting student data.